The Mediating Role of Frustration Tolerance in the Relationship Between Early Maladaptive Schemas, Self-Differentiation, and Marital Conflict in Individuals Applying for Divorce - Hosseini, Samira; Mousavi, Said Ali mohammad; Shomalyoskoei , Arezoo (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study aimed to determine the fit of a structural equation model examining the mediating role of frustration tolerance in the relationship between early maladaptive schemas and self-differentiation with marital conflict among individuals applying for divorce. Methods and Materials: This study employed a fundamental, descriptive-correlational design using structural equation modeling (SEM). The statistical population consisted of individuals applying for divorce who had active cases in family counseling centers affiliated with the judiciary in Karaj and Hashtgerd between February 2025 and October 2025. A sample of 250 participants (139 women and 111 men) was selected through convenience sampling. Data were collected using the Revised Marital Conflict Questionnaire (Sanaei et al., 2008), the Young Schema Questionnaire (Young, 2005), the Self-Differentiation Inventory (Skowron & Friedlander, 1998), and the Frustration Discomfort Scale (Harrington, 2005). Data analysis was conducted using SPSS version 27 and AMOS version 26 with maximum likelihood estimation. Findings: The results indicated that the proposed structural model demonstrated an acceptable fit with the data (χ²/df = 1.49, GFI = 0.908, CFI = 0.958, RMSEA = 0.044). Early maladaptive schemas had a positive and significant effect on marital conflict (β = 0.412, p = .001), whereas self-differentiation had a negative and significant effect (β = −0.374, p = .001). Frustration tolerance (operationalized as intolerance) showed a positive and significant relationship with marital conflict (β = 0.424, p = .001). Moreover, frustration tolerance significantly mediated the relationships between early maladaptive schemas and marital conflict (β = 0.157, p = .001) and between self-differentiation and marital conflict (β = −0.138, p = .001). The model explained 57% of the variance in marital conflict (R² = 0.57). Conclusion: The findings suggest that early maladaptive schemas and self-differentiation are significant predictors of marital conflict, both directly and indirectly through frustration tolerance.